The Life of Nuns: Love, Politics, and Religion in Medieval German Convents - Lähnemann, Henrike (Open Book Publishers, 2024)
This book explores the lives of nuns in medieval German convents, focusing on their roles in love, politics, and religion. It highlights how these women held significant influence as 'brides of Christ' and played vital roles within their communities. The authors, Henrike Lähnemann and Eva Schlotheuber, delve into various aspects of convent life, including education, family dynamics, music, and the impact of the Reformation. The work draws from unique historical sources, such as a convent diary and a collection of letters, to provide insight into the nuns' experiences and their resistance to Lutheran reforms. Aimed at those interested in medieval history and women's roles in religious contexts, the book seeks to illuminate the overlooked contributions of these nuns